Quantification of Chaotic Intrinsic Variability of Sea‐Air CO2 Fluxes at Interannual Timescales. Issue 22 (10th November 2020) - Gehlen, M.; Berthet, S.; Séférian, R.; Ethé, Ch.; Penduff, T.
Abstract: Chaotic intrinsic variability (CIV) emerges spontaneously from nonlinear ocean dynamics even without any atmospheric variability. Eddy‐permitting numerical simulations suggest that CIV is a significant contributor to the interannual to decadal variability of physical properties. Here we show from an ensemble of global ocean eddy‐permitting simulations that large‐scale interannual CIV propagates from physical properties to sea‐air CO2 fluxes in areas of high mesoscale eddy activity (e.g., Southern Ocean and western boundary currents). In these regions and at scales larger than 500 km (~5°), CIV contributes significantly to the interannual variability of sea‐air CO2 fluxes. Between 35°S and 45°S (midlatitude Southern Ocean), CIV amounts to 23.76 TgC yr −1 or one half of the atmospherically forced variability. Locally, its contribution to the total interannual variance of sea‐air CO2 fluxes exceeds 76%. Outside eddy‐active regions its contribution to total interannual variability is below 16%. Plain Language Summary: Sea‐air CO2 fluxes undergo substantial regional and interannual fluctuations. These fluctuations are mostly forced by changes in large‐scale atmospheric patterns, but ocean internal dynamics could also contribute to them. This study quantifies these two sources of variability and their contributions to fluctuations of sea‐air CO2 fluxes over large oceanic regions. It relies on the analyses of three ocean numerical simulations driven by the same atmospheric forcing but starting from small differences in initial conditions, and including a simplified representation of marine ecosystems. Simulations are run at a horizontal resolution allowing to model part of the effect of ocean mesoscale activity on physical and chemical tracers. We demonstrate that nonlinear oceanic processes drive fluctuations of sea‐air CO2 fluxes at interannual timescales that are inherently random. The magnitude of these fluctuations is substantial over areas of high kinetic energy and locally exceeds 76% of the total interannual variance of sea‐air CO2 fluxes. Key Points: Interannual chaotic intrinsic (CIV) variability propagates from physical to chemical tracers in areas of strong mesoscale activity It contributes significantly to interannual variability of sea‐air CO2 fluxes over the Southern Ocean and western boundary current systems CIV is small outside eddy‐active regions where interannual variability of sea‐air CO2 fluxes is prominently driven by atmospheric forcing